Integrative Analysis of PAIP2B to Identify a Novel Biomarker for Pancreatic Ductal Adenocarcinoma - Xiang, Yaoxian; Wang, Li; Cheng, Yurong; An, Huanjuan; Zhang, Chan; Wang, Jing; Tong, Yingying; Yan, Dong (Global Medical Genetics, 2023)
The aim of the study was to evaluate the potential diagnostic and prognostic value of gene, Poly A-Binding Protein Interacting Protein 2B (PAIP2B) in pancreatic cancer. We used the gene expression data and clinical information of pancreatic adenocarcinoma patients from The Cancer Genome Atlas database and Gene Expression Omnibus database to analyze the expression of PAIP2B in pancreatic cancer samples, and validated the expression of PAIP2B in tumor tissue, using bioinformatics technology to explore the prognostic value of PAIP2B and its possible biological function. A significantly lower level of PAIP2B was observed in pancreatic cancer patients than in controls, and validated by immunohistochemistry. PAIP2B reduced the proliferation and invasion of cancer cells and had a significantly high expression in early stage. Patients with lower levels of PAIP2B had a significantly shorter median survival time than those with higher levels. DNA demethylation played an important role in PAIP2B expression. In addition, PAIP2B expression was significantly associated with the tumor-infiltrating immune cells, especially T cells CD8, T cells CD4 memory resting, macrophages M0, and dendritic cells resting. Our study also found that PAIP2B regulated miRNA function leading to disease progression in pancreatic cancer patients. Our study explored the potential value of PAIP2B as a biological link between prognosis and pancreatic cancer, and provided reference for the follow-up study on the role of PAIP2B in pancreatic cancer.
Keywords: pancreatic carcinoma; PAIP2B; overall survival; prognosis; biomarker